Large Genomic Rearrangements of Desmosomal Genes in Italian Arrhythmogenic Cardiomyopathy Patients. (October 2017) - Pilichou, Kalliopi; Lazzarini, Elisabetta; Rigato, Ilaria; Celeghin, Rudy; De Bortoli, Marzia; Perazzolo Marra, Marina; Cason, Marco; Jongbloed, Jan; Calore, Martina; Rizzo, Stefania; Regazzo, Daniela; Poloni, Giulia; et al.
Abstract : Background: Arrhythmogenic cardiomyopathy (AC) is an inherited heart muscle disease associated with point mutations in genes encoding for cardiac desmosome proteins. Conventional mutation screening is positive in ≈50% of probands. Copy number variations (CNVs) have recently been linked to AC pointing to the need to determine the prevalence of CNVs in desmosomal genes and to evaluate disease penetrance by cosegregation analysis in family members. Methods and Results: A total of 160 AC genotype-negative probands for 5 AC desmosomal genes by conventional mutation screening underwent multiplex ligation-dependent probe amplification. Nine heterozygous CNVs were identified in 11 (6.9%) of the 160 probands. Five carried a deletion of the entire plakophilin-2 ( PKP2 ) gene, 2 a deletion of only PKP2 exon 4, 1 a deletion of the PKP2 exons 6 to 11, 1 a PKP2 duplication of 5′ untranslated region till exon 1, 1 the desmocollin-2 ( DSC2 ) duplication of exons 7 to 9, and 1 a large deletion of chromosome 18 comprising both DSC2 and desmoglein-2 genes. All probands were affected by moderate-severe forms of the disease, whereas 10 (32%) of the 31 family members carrying one of these deletions fulfilled the diagnostic criteria. Conclusions: Genomic rearrangements were detected in ≈7% of AC probands negative for pathogenic point mutations in desmosomal genes, highlighting the potential of CNVs analysis to substantially increase the diagnostic yield of genetic testing. Genotype–phenotype correlation demonstrated the presence of the disease in about one third of family members carrying the CNV, underlying the role of other factors in the development and progression of the disease. Abstract : Supplemental Digital Content is available in the text.